2018
DOI: 10.26552/ems.2018.2.46-56
|View full text |Cite
|
Sign up to set email alerts
|

Smart Services and Their Benefits for Manufacturers From a Global Perspective

Abstract: Current manufacturers do not provide only tangible products to their customers, but also deliver services and integrated solutions in today's globalized environment. Furthermore, they effort also on implementing 'smart services'. Smart services allow by connected productservice systems to exchange data between their customers and the service providers. Smart services offer many benefits for both manufacturing companies as service providers and as well as for their customers. The aim of this paper is to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Numerous studies can be found which focus on bankruptcy prediction in Slovakia (Kovacova et al 2018), Slovak research on identifying significant sources of enterprise goodwill (Kliestik et al 2018a), or using controlling as a competitiveness tool on the Slovak market (Vagner 2016), but detection of the existence and the development of quality cultures in the context of Industry 4.0 is still lacking. It is necessary to examine these facts, as Kanovska (2018) notes that smart manufacturing is still developing and taking place in different forms. Krajcsak (2018) finds ISO standards and Total Quality Management (TQM) only appropriate organisational cultures, not quality culture; this is another scientific gap when it comes to determining a representative culture quality for traditional quality concepts.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies can be found which focus on bankruptcy prediction in Slovakia (Kovacova et al 2018), Slovak research on identifying significant sources of enterprise goodwill (Kliestik et al 2018a), or using controlling as a competitiveness tool on the Slovak market (Vagner 2016), but detection of the existence and the development of quality cultures in the context of Industry 4.0 is still lacking. It is necessary to examine these facts, as Kanovska (2018) notes that smart manufacturing is still developing and taking place in different forms. Krajcsak (2018) finds ISO standards and Total Quality Management (TQM) only appropriate organisational cultures, not quality culture; this is another scientific gap when it comes to determining a representative culture quality for traditional quality concepts.…”
Section: Introductionmentioning
confidence: 99%
“…Brand is a very important factor that affects the perceptions and evaluations of customer. Many authors agree that a brand evokes in consumers emotions influenced by their experience with the brand (Krizanova et al, 2013, Krizanova & Majerova, 2015Kliestikova et al, 2019;Mirica, 2018;Kanovska, 2018;Mala & Bencikova, 2018). Branding is considered a separete marketing tool, which is an important factor -it is the product feature that distinquishes it from competing products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The brand strikes an emotion in consumers. This is a combination of consumer experience with the brand since the very first "touch" of the product [3,4,5,6]. Brands have a different meaning for each consumer, which helps develop the purchasing trends.…”
Section: Literature Reviewmentioning
confidence: 99%